Controlling supramolecular chirality of two-component hydrogels by J-and H-aggregation of building blocks - Liu, Guofeng (2020)
While manipulating the helicity of nanostructures is a challenging task, it attracts great research interest on account of its crucial role in better understanding the formation mechanisms of helical systems. For the supramolecular chirality in self-assembly systems, one challenge is how to understand the origin of supramolecular chirality and inherent helicity information on nanostructures regulated by functionality-oriented stacking modes (such as J- and H-aggregation) of building blocks. Herein, two-component hydrogels were prepared by phenylalanine-based enantiomers and achiral bis(pyridinyl) derivatives, where helical nanofibers with inverse handedness as well as controllable helical pitch and diameter were readily obtained through stoichiometric coassembly of these building blocks. The helix inversion was achieved by the transition between the J- and H-aggregation of bis(pyridinyl) derivatives, which was collectively confirmed by circular dichroism, scanning electron microscopy, Fourier transform infrared spectroscopy, and single X-ray crystallography. Interestingly, the helical coassemblies with opposite handedness could be obtained not only from the enantiomeric building blocks but also from the chiral monomers with the same configurational chirality by exchanging achiral additives. This work provides insight into the origin and helicity inversion of supramolecular chirality in molecular self-assembly systems and may shine light on the precise fabrication of chiral nanostructures for potential applications in smart display devices, optoelectronics, and biological systems.